Applied evolutionary economics : new empirical methods and simulation techniques - Saviotti, Pier Paolo (Cheltenham: Edward Elgar, 2002)
The book examines recent developments in empirical methods and applied simulation in evolutionary economics.The book will be of great interest to researchers of evolutionary economics and technological innovation.
Includes bibliographical references and index.
rpm 24/10/13
Loan
Keywords: Evolutionary economics; Technological innovation